New Private Infrastructure Projects in Developing Countries Have Started Being Affected by the Financial Crisis - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
New private activity continued to take place in developing countries in Aug-Nov 2008 with projects being developed, tendered, and taken to financial close, but at a rate that was about 40 percent lower than in the same period in 2007. The slowdown reflects an initial impact of the financial crisis which has made financing more onerous and difficult to secure as access to capital markets and bank lending has been reduced or halted and risk perception increased. Projects are facing higher cost of financing, but the major impact to date is project being delayed or cancelled. It is, however, too early to assess the full impact of the crisis on new Public-Private Investment (PPI) projects. Many investors and financiers are in a wait-and-see mindset and are likely to be so for the next 3 to 6 months or until the breadth and depth of the crisis impact become clearer. When financial markets bottom out or start to recover, project financing levels are likely to remain impacted over a significant period of time if the trends shown in previous financial crises are repeated. As the "flight to quality" sets in for banks and other financiers, the likely impact will be more stringent financial conditions, not only via higher cost of financing but also with lower debt/equity ratios and more conservative structures. The expected economic downturn in developed and developing countries is also likely to reduce demand levels and have a significant impact on project revenues, and consequently on projects' financial viability.